2002
DOI: 10.1007/s00442-001-0818-z
|View full text |Cite
|
Sign up to set email alerts
|

Physiological ramifications of habitat selection in territorial male ovenbirds: consequences of landscape fragmentation

Abstract: Since boreal forest fragments are of lower quality than contiguous forest for breeding Ovenbirds (Seiurus aurocapillus), we predicted that competition for breeding sites in contiguous forest should lead to a greater prevalence of individuals in better condition in these habitats. We quantified male condition using morphological and hematological indices. Males in contiguous forest were larger than males in forest fragments and had higher hematocrits and mean corpuscular volumes, as well as a greater prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 46 publications
3
32
0
1
Order By: Relevance
“…Other ecological studies have suggested that the ratio between two avian leukocytes, the heterophil/lymphocyte (H/L) ratio, provides an indicator of overall stress levels of individual birds (e.g., Gross and Siegel, 1983;Vleck et al, 2000;Ruiz et al, 2002). Finally, leukocyte differentials and H/L ratios have been used in recent studies to demonstrate links between stress and territory quality (Mazerolle and Hobson, 2002) and trade-offs between reproductive effort and immune function (Norris and Evans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Other ecological studies have suggested that the ratio between two avian leukocytes, the heterophil/lymphocyte (H/L) ratio, provides an indicator of overall stress levels of individual birds (e.g., Gross and Siegel, 1983;Vleck et al, 2000;Ruiz et al, 2002). Finally, leukocyte differentials and H/L ratios have been used in recent studies to demonstrate links between stress and territory quality (Mazerolle and Hobson, 2002) and trade-offs between reproductive effort and immune function (Norris and Evans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Note that each of these affected species can be characterized as "interior species" that specialize on deep forest habitat. These species should be particularly prone to forest fragmentation effects (Bender et al 1998), and the physiological data suggest that this prediction is met (but see Mazerolle and Hobson 2002 who showed that increased territory defense in contiguous forests results in high energetic demand and reduced immunological condition compared with birds in fragmented forest).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of relationships between the BCIs and blood variables other than Hb and Hct suggested that these other variables generally had little value as condition indicators for 12-day old Welcome Swallow nestlings. However, some of them are correlated with body condition or fitness-related traits in some other bird species: (1) MCV was correlated with aspects of breeding affecting reproductive output in adult Arctic Skuas Catharcta skua (Bearhop et al, 1999), with potential exposure to greater intraspecific competition in male Ovenbirds Seiurus aurocapillus (Mazerolle and Hobson, 2002) and with greater survival to fledging in nestling Great Tits (Nadolski et al, 2006); (2) MCH was correlated with fledging success in nestling Great Tits (Nadolski et al, 2006); and (3) WBC was correlated with body condition (sizeadjusted mass) in nestling Burrowing Parrots Cyanoliseus patagonus (Masello et al, 2009) and with post-fledging survival in Wood Storks Mycteria americana (Hylton et al, 2006). However, some of these blood variables are not correlated with body condition or traits that influence fitness in other bird species (e.g.…”
Section: Lack Of Relationships Between Other Blood Variables and Condmentioning
confidence: 99%